Sejarah Dan Pemikiran Kaum Injili Di Tengah-Tengah Perubahan Dan Tantangan Zaman - Enggar Objantoro (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat)
Enggar Objantoro, History and Thought of Evangelicals Amidst the Changes and Challenges of the Age. In this paper the author discusses the existence and challenges that are being and will be faced by evangelicals, especially in Indonesia. To be able to describe what the purpose of the study, the author uses  the descriptive research literature study. The analysis in this study focuses on the interpretation of written materials in accordance with the context. To maintain credibility, the authors use authentic and published literature material. The results of this study show that the presence of evangelicals in some places has interesting characteristics to investigate, as in America can not be released with Fundamentalism. Then evangelicals in Europe have existed since the time of reform, because evangelicals are understood as reformed churches. In 1842 the UK also established the European Evangelical Alliance, which has contributed to the formation of the evangelical movement in Europe. The rise of evangelicals in Indonesia is also inseparable from the evangelical movement in America. Several evangelical mission organizations are present in Indonesia. The evangelicals are in the midst of the changing times that are influenced by various understandings. Responding to the changing times there are several things that evangelicals need to do: hold fast to God's truth, open to other views without going with the flow, active in conveying ideas.